2021
DOI: 10.1002/advs.202004262
|View full text |Cite
|
Sign up to set email alerts
|

15.3% Efficiency All‐Small‐Molecule Organic Solar Cells Achieved by a Locally Asymmetric F, Cl Disubstitution Strategy

Abstract: Single junction binary all-small-molecule (ASM) organic solar cells (OSCs) with power conversion efficiency (PCE) beyond 14% are achieved by using non-fullerene acceptor Y6 as the electron acceptor, but still lag behind that of polymer OSCs. Herein, an asymmetric Y6-like acceptor, BTP-FCl-FCl, is designed and synthesized to match the recently reported high performance small molecule donor BTR-Cl, and a record efficiency of 15.3% for single-junction binary ASM OSCs is achieved. BTP-FCl-FCl features a F,Cl disub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 46 publications
0
65
0
Order By: Relevance
“…A PCE of over 15% has already been realized by NFA based OSCs containing elaborately designed BDT donors. 25–30 Meanwhile, in spite of much lower synthetic cost, the development and PCEs of oligothiophene based donors have been unsatisfactory. From the era of fullerene acceptors to the present era inaugurated by NFAs, oligothiophene donors have been intensively investigated as electron-donating materials in organic photovoltaic research and technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A PCE of over 15% has already been realized by NFA based OSCs containing elaborately designed BDT donors. 25–30 Meanwhile, in spite of much lower synthetic cost, the development and PCEs of oligothiophene based donors have been unsatisfactory. From the era of fullerene acceptors to the present era inaugurated by NFAs, oligothiophene donors have been intensively investigated as electron-donating materials in organic photovoltaic research and technology.…”
Section: Introductionmentioning
confidence: 99%
“…All top BDT donors (PCE > 15%), without exception, are featured with the A–π–D–π–A backbone. 25–30 However, for high performance oligothiophene donors, it has been found that probably the A–π–A′–π–A structure is a more suitable design. Previously, by replacing the electron-donating central thienyl unit of DRCN7T with an electron-withdrawing di-chlorinated thienyl unit, SM donor 2Cl7T (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Thus, all-small-molecule (ASM) OSCs based on both SM donors and non-fullerene SM acceptors may be promising candidates of new-generation high performance OSCs. 8,10,[17][18][19][20][21][22] To date, the highest PCE of binary ASM OSCs has reached 15.3%, 19,23 but it is still lower than the polymer-based OSCs (~18%). [1][2][3][4] Since the potential of the best non-fullerene FREAs has been proved in the high efficiency polymer-based OSCs, for ASM OSCs, its main task now is to improve available SM donor materials or find new promising SM donors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10–14 ] As a result, small‐molecule donors have high potentials for industrial application. However, the state‐of‐the‐art PCEs of single‐junction all‐small‐molecule (ASM) OSCs reach over 14%, [ 15–23 ] which are still lower than that of polymer‐based OSCs. The major challenge for further improving the PCEs of small molecule OSCs is to control the interpenetrating network of the donor/acceptor blends.…”
Section: Introductionmentioning
confidence: 99%